The Predictive Ability of Hepatic Steatosis Index for Gestational Diabetes Mellitus and Large for Gestational Age Infant Compared with Other Noninvasive Indices Among Chinese Pregnancies: A Preliminary Double-center Cohort Study - Song, Shuoning; Duo, Yanbei; Zhang, Yuemei; Qiao, Xiaolin; Xu, Jiyu; Zhang, Jing; Peng, Zhenyao; Chen, Yan; Nie, Xiaorui; Sun, Qiujin; Yang, Xianchun; Wang, Ailing; et al. (Diabetes, metabolic syndrome and obesity, 2021)
To evaluate the association of hepatic steatosis index (HSI) in the first trimester and the risk of gestational diabetes mellitus (GDM) as well as large for gestational age (LGA) infant in Chinese women. A total of 1082 pregnant women were included in this study. Maternal basic laboratory data, including ALT, AST, FBG, insulin, TG, and HDL-C, were tested during 6-12 weeks of gestation and anthropometric characteristics were monitored during gestation. A 75-g oral glucose tolerance test (OGTT) was conducted at 24-28 weeks of gestation. HSI, nonalcoholic fatty liver disease (NAFLD) liver fat score, triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) and triglyceride-glucose (TyG) index were calculated. Odds ratio with 95% confidence interval for subsequent risk of GDM and LGA by HSI quartiles were assessed by binary logistic regression model. The predictive ability of HSI for GDM and LGA was evaluated by the receiver operating characteristic (ROC) curve analysis and was compared with other indices. The incidence of GDM and LGA were 22.09% (239/1082) and 10.53% (87/826). HSI was higher in GDM group than in NGT group (median, interquartile range: 30.67, 27.20-35.10 vs 27.98, 25.70-30.82, <0.001). Incidence of GDM was gradually increased with increasing HSI values. Women in the highest HSI quartile had significantly higher risk of LGA delivery than those in the lowest HSI quartile ( <0.05). The area under the ROC curves of HSI for GDM and LGA were higher than other indices, reaching 0.646 (95%CI: 0.605-0.686) and 0.600 (95%CI: 0.541-0.660), respectively. Higher HSI was independently associated with higher risk of GDM and LGA in Chinese women. HSI in the first trimester can predict the risk of GDM and LGA.